Technological Transformation of the Public Distribution System: Prospects and Challenges - Raj, Tilak; Anuradha (Gyan Management Journal, 2017)
Technology based reforms in Government policies can improve transparency and accountability, curtail corruption and make Government programs more efficient. But while implementing these reforms Government faces several challenges which needs due attention and also it is necessary to study its different prospects. Therefore, keeping all above in mind this paper looks into the role of technology in strengthening and reforming the working of current public distribution system through studying its different prospects and challenges. The study is based on secondary data collected from various sources i.e., journals, books, research papers and websites particularly from Department of Food and Public Distribution, Economic Survey etc. The study concluded that the technology initiative has improved efficiency of PDS, but still there are many problems in the usage of new technology due to lack of awareness, connectivity issue sand failure of technical infrastructure.